The Role of the Prosecutors in Implementing the Eradication of Corruption Crime - Luhur Supriyohadi; Sri Kusriyah; Widayati Widayati (Law Development Journal, 2022)
The purpose of this study is to examine and analyze the role of the Prosecutor's Office in eradicating corruption. In this paper, the writer uses the normative juridical method with the specifications of analytical descriptive writing. The Prosecutor's Office has the authority to assess the results of investigations carried out by the police, on the other hand, the Prosecutor's Office is also authorized to carry out or stop prosecutions. Thus, it is no exaggeration to say that the Prosecutor's Office plays a very vital role in the criminal justice system. The Prosecutor's Office is the controller of the case process (dominus litis), and has a central position in law enforcement, because only the Prosecutor's Office can determine whether a case can be brought to court or not based on valid evidence according to the Criminal Procedure Code. The role of the Prosecutor's Office in eradicating criminal acts of corruption begins when the case has not been transferred to the Court until the implementation of the court's decision. However, in the case of corruption, the Prosecutor's Office has the authority to act as a public prosecutor as well as an investigator. The authority of the prosecutor as a special criminal investigator is regulated by Act No. 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia in Article 30 paragraph (1) letter d. In addition, in its role in eradicating corruption, the Prosecutor's Office continues to coordinate with the police and the Corruption Eradication Commission.